An Amplicon Panel for High-Throughput and Low-Cost Genotyping of Yesso Scallop Mizuhopecten yessoensis - Ben J. G. Sutherland; Chen Yin Walker; Denman Moody; Chelsea Bennett; Marissa Wright-LaGreca; Chloe Shamash-McLaughlin; Karen Leask; Daniel Roth; Megan Lebeuf; Timothy J. Green (Marine Biotechnology, 2026)

Beyond NAMs versus animal models: Context of use as the governing framework for integrated nonclinical strategies in drug development - Stefano Gaburro; Brian Berridge; Nicholas W. Kelley; Eckhard von Keutz; Marc Ferrer; Clive Roper; Michael J. Fossler; Jeffrey J. Bajramovic; Jean-Pierre Valentin; Timothy McGovern; Todd Bourcier; Ronald L. Wange; et al. (Regulatory Toxicology and Pharmacology, 2026)

Act fast: improved control of Rhamnus cathartica with rapid foliar herbicide and herbaceous seeding - Andrew D. Kaul; Peter D. Wragg; Peter B. Reich; Alex M. Roth; Paul J. Bockenstedt; Michael J. Schuster (Forest Ecology and Management, 2026)

July in focus in HCB: impact of environmental radiation on cells and tissues - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2026)

June in focus in HCB: advanced methodologies - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2026)

Calcium and calpastatin delay proteolysis early during beef maturation - J.S. Bodmer; M. Beline; C.N. Yen; M. Zumbaugh; J.C. Wicks; E.C. Roth; J. Chen; M. Koohmaraie; S. Matarneh; T.H. Shi; S.L. Silva; D.E. Gerrard (Meat Science, 2026)

Differential motor unit firing rate and hypertrophic adaptations of the vastus lateralis despite similar strength increases following high-load versus combined high- and low-load resistance training interventions - Alex A. Olmos; Daniel J. Lawson; Stephanie A. Sontag; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Allen L. Redinger; Sean M. Gamache; Michael A. Trevino (Experimental Brain Research, 2026)

May in focus in HCB: organelles—mitochondria and peroxisomes - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2026)

April In focus in HCB: skeletal muscle fibers - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2026)

Nasal hormone administration can support ambystomid salamander ex situ conservation breeding programs - Devin M. Chen; Carrie K. Kouba; Terri L. Roth; Peter J. Allen; Nucharin Songsasen; Andrew J. Kouba (Journal for Nature Conservation, 2026)

Oh deer! Videography reveals a range of defensive behaviors against a cervid by a ground‐nesting bird - Kylie L. Brunette; Amber M. Roth; Rachel L. Darling; Michael L. Peters; Erik J. Blomberg (Ecology, 2026)

Variability in Fecundity–Body Size Relationships for Atlantic Salmon Associated With Body Condition and Life History - Tara L. Imlay; Cindy Breau; Julien April; J. Brian Dempson; John Hayward; Jason LeBlanc; Jenny E. Reid; David Roth; Jamie T. Vallis; Travis E. Van Leeuwen; Laura K. Weir (Fisheries Management and Ecology, 2026)
While body size is the primary driver of fecundity, other factors may contribute to variation in these relationships. Anadromous populations of Atlantic salmon ( Salmo salar ) have diverse life histories, and fisheries management relies on accurate fecundity estimates. We used Bayesian hierarchical models to determine the relationship between fecundity and fork length, and other life‐history characteristics, for 25 spawning populations throughout Eastern Canada. Fecundity was best modeled at the river level, increased with body size and condition, and decreased with mean egg diameter. Fecundity was higher for individuals that spent fewer years in freshwater as juveniles, and for consecutive repeat spawners compared with first‐time (or maiden) spawners that spent 1 year in the ocean. Lastly, there was interannual variability in the fecundity–body size relationship. These relationships should be used in conjunction with data on recent changes in body size and/or life‐history traits of populations to inform stock management.

Process-based cost assessment of electrochemical metals recovery from municipal solid waste incineration ash - Jacqueline E. Baidoo; Richard Roth; Duhan Zhang; Michael J. Wang; Yet-Ming Chiang; Elsa A. Olivetti (Waste Management, 2026)

Correction: The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2026)

March In focus in HCB: the “speckled” nucleus - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2026)

February in focus in HCB: spatial transcriptomics - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

January in focus in HCB: antibody validation - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2026)

Ocean acidification in Canada: the current state of knowledge and pathways for action - Kristina M. Barclay; Helen J. Gurney-Smith; Mohamed Ahmed; James R. Christian; Frédéric Cyr; Patrick J. Duke; Brent G. T. Else; Iria Gimenez; Martine Lizotte; M. Catherine Reader; Myron Roth; Krysten Rutherford; et al. (Frontiers in Marine Science, 2026)
Ocean acidification (OA) generally receives far less consideration than other climate stressors and related hazards, such as global warming and extreme weather events. Canada is uniquely vulnerable to OA given its extensive coastal oceans, the oceanographic processes in its three basins, accelerated warming and sea-ice melt, and extensive coastal communities and maritime economic sectors. Canada’s coastline is also home to extensive and diverse First Nations peoples with distinct histories, rights, title, laws, governance and whose traditions and cultures are extrinsically linked to the sea. However, there are currently very limited pathways to support OA action, mitigation, and/or adaptation in Canada, particularly at the policy level. Here, we present a first synthesis of the current state of OA knowledge across Canada's Pacific, Arctic, and Atlantic regions, including monitoring, modelling, biological responses, socioeconomic and policy perspectives, and examples of existing OA actions and efforts at local and provincial levels. We also suggest a step-wise pathway for actions to enhance the coordinated filling of OA knowledge gaps and integration of OA knowledge into decision-making frameworks. The goals of these recommendations are to improve our ability to respond to OA in Canada, and minimize risks to coastal marine environments and ecosystems, vulnerable sectors, and communities.

A Snapshot of the Ecological Contributions of an Active Coral Restoration Effort in an Indo-Pacific Reef - Henriikka Malkamäki; Rinaldi Gotama; Lauren D. Sparks; Serena J. Stean; Rahmadi Prasetijo; Florian Roth; Pascal Sebastian (Thalassas: An International Journal of Marine Sciences, 2025)
Active coral restoration is promoted to rebuild reef ecosystems, yet its ecological contributions remain uncertain. We conducted a field experiment across three sites in Nusa Penida Marine Protected Area (MPA): a natural site as the closest reference to the reef’s original state, a rubble site degraded by anthropogenic stressors, and a restoration site (est. 2020) with a monoculture of transplanted Acropora pulchra . We compared benthic cover, fish assemblages, and early succession using ceramic settlement tiles deployed for five durations (6, 8, 10, 12, and 25 weeks). The natural site supported the highest coral cover (40.2% ± 10.96 SE), 47 fishes (19 unique), and commercially important piscivores ( Cephalopholis spp., Lutjanus decussatus , Caranx melampygus ). The rubble site showed low coral cover (13.5% ± 4.53 SE), 32 fishes (9 unique), and detritivore dominance. The restoration site had intermediate coral cover (34.1% ± 11.83 SE) and 40 fishes (16 unique), but no piscivores. Settlement tile experiments revealed coral settler densities (0.028–0.125 cm⁻²) comparable to other Indo-Pacific reefs, but no significant differences among sites. Coral settlement peaked at 10 weeks but declined thereafter, likely due to competition. While crustose algae and other reef binders were abundant, loose rubble likely inhibited substrate consolidation and coral attachment at the rubble site. In both the natural and restoration site, overgrowing phototrophic sponges emerged as a potential threat to corals. Our results suggest that while restoration can enhance habitat structure and fish diversity, trophic rebuilding and long-term coral recruitment may still be limited, highlighting the need for continued monitoring and longer-term assessments. These findings offer insights into restoration potential and ecological conditions in Nusa Penida MPA to enhance reef resilience and management.

December In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

November in focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

October in focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

September in focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

August in focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

July in focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

June in focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

March in focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

May In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

April In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

February In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

January In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2025)

The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2025)

Recovery of ecosystem carbon pools 35 years after whole-tree and stem-only clearcutting a red spruce – balsam fir forest in north-central Maine, USA - Inge Stupak; Bruna Barusco; Russell D. Briggs; Ivan J. Fernandez; Shawn Fraver; Agnė Grigaitė; Christopher Preece; Brian E. Roth; C. Tattersall Smith (Forest Ecology and Management, 2025)

Interrelationships among methods of estimating microbial biomass across multiple soil orders and biomes - Z.W. Buell; J. Dabbs; J.M. Steinweg; L.A. Kluber; J.R. Phillips; Z.K. Yang; S.W. Roth; R.M. Miller; J.L.M. Gutknecht; C.W. Schadt; M.A. Mayes (Soil Biology and Biochemistry, 2025)

Air pollution exposure assessment for preschool children: Addressing spatial and temporal variations and social inequities - Å.K. Watne; M. Azzouz; P. Molnar; L. Stockfelt; J. Lindén; E. Johansson; M. Laurelin; T. Wisell; H. Lundström; A. Roth; S. Jutterström; J. Moldanova; et al. (Journal of Environmental Management, 2025)

Long-term field study on corn response to sulfur fertilization in Iowa, USA - Cecilia Crespo; John L. Kovar; Chad E. Hart; Richard T. Roth; Peter L. O’Brien; Sabrina J. Ruis (Field Crops Research, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Revegetation of Elymus grasses suppresses invasive Rhamnus cathartica in deciduous forest understories - Michael J. Schuster; Peter D. Wragg; Alex M. Roth; Paul Bockenstedt; Lee Frelich; Peter B. Reich (Ecological Engineering, 2025)

Centenarians—the way to healthy vascular ageing and longevity: a review from VascAgeNet - Sabrina Summer; Maria Borrell-Pages; Rosa-Maria Bruno; Rachel E. Climie; Konstantina Dipla; Aysenur Dogan; Kseniia Eruslanova; Emil Fraenkel; Francesco Mattace-Raso; Christopher J. A. Pugh; Keith D. Rochfort; Mark Ross; et al. (GeroScience, 2024)
The prevalence of centenarians, people who lived 100 years and longer, is steadily growing in the last decades. This exceptional longevity is based on multifaceted processes influenced by a combination of intrinsic and extrinsic factors such as sex, (epi-)genetic factors, gut microbiota, cellular metabolism, exposure to oxidative stress, immune status, cardiovascular risk factors, environmental factors, and lifestyle behavior. Epidemiologically, the incidence rate of cardiovascular diseases is reduced in healthy centenarians along with late onset of age-related diseases compared with the general aged population. Understanding the mechanisms that affect vascular ageing in centenarians and the underlying factors could offer valuable insights for developing strategies to improve overall healthy life span in the elderly. This review discusses these key factors influencing vascular ageing and how their modulation could foster healthy longevity.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

Cortical drive may facilitate enhanced use of the paretic leg induced by random constraint force to the non-paretic leg during walking in chronic stroke - Hyosok Lim; Shijun Yan; Weena Dee; Renee Keefer; Iram Hameeduddin; Elliot J. Roth; William Z. Rymer; Ming Wu (Experimental Brain Research, 2024)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Research participant perceptions of personal utility in disclosure of individual research results from genomic analysis - Brenda Bogaert; Marie-Josée Crevier; Cindy Roth; Ralf J. Jox; Gaia Barazzetti (Journal of Community Genetics, 2024)
This article elaborates research participant perspectives on the communication of individual research results from genomic analyses. While most analyses focus on how to communicate results from the perspectives of clinicians or researchers, there is insufficient data on user perspectives and how this information may be used, valued, and interpreted by patients and their families. The concept of personal utility, which considers factors related to quality of life, including on how information may impact the person’s future decisions, has been shown to be particularly relevant to understand research participant perspectives and to move beyond clinical and analytic utility factors such as mortality and morbidity. This article draws from qualitative research of research participants awaiting genomic results in the case of sudden cardiac death. Our results show perspectives of personal utility in communication of genomic results, including cognitive, behavioral, and affective outcomes. Cognitive outcomes include gain of information, improved knowledge of etiology and inheritance characteristics, and curiosity for what might be found. Behavioral outcomes include being able to plan life decisions, while affective outcomes include various coping strategies used. We will also discuss the value of knowing negative results and incidental findings from the research participant’s perspective. This contribution gives suggestions on best practices to guide genome analysis returns, including incorporating participant wishes on individualized communication at the consent stage; developing relational autonomy approaches; and engaging them throughout the research trajectory.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

Trophic Structure and a Temporal Shift in Trophic Diversity of Mobile Consumers in a Subarctic Estuary - Jillian R. St. George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuaries and Coasts, 2024)
Quantifying trophic relationships within and between species in terms of trophic position, ontogeny and trophic diversity provides information on community-level structure and function. Little attention has been focused on examining the trophic structure and temporal changes of communities in freshwater-marine coupled systems in the subarctic and associated impacts of anthropogenic activity on trophic interactions. Therefore, the objective of this study was to quantify the trophic position of mobile consumers (15 species in total) within the lower Churchill River area (Churchill, Manitoba, Canada), examine trophic position variation in relation to ontogeny, and measure the trophic diversity of a fish assemblage before (1993–1995) and after (2019–2020) the installation of the Churchill River weir in the late 1990s. We used stable isotopes (δ 13 C and δ 15 N) to quantify individual and group-level variation in trophic position of thirteen fish species and two seal species and also assessed six community-level metrics of a three fish species assemblage between time periods. Overall, species that mainly foraged on freshwater resources occupied lower trophic positions than species that mainly consumed marine resources. Trophic position increased with fish age only in cisco, fourhorn sculpin, Greenland cod and northern pike. A temporal shift from a trophically diverse to a more trophically redundant fish assemblage occurred between 1993–1995 and 2019–2020. As a result, these predator species now play similar trophic roles. Information on the long-term change in trophic structure of this sub-Arctic estuarine system may help with understanding how anthropogenic activity and climate change have influenced the trophic diversity of a fish assemblage inhabiting this system.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2024)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

Editorial: Histochemistry and Cell Biology implements new submission guidelines for image presentation and image analysis - Douglas J. Taatjes; Takehiko Koji; Michael Schrader; Jürgen Roth (Histochemistry and Cell Biology, 2023)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

Thermal hazards assessment of three azo nitrile compounds - Cuixian Yang; Dylan Aljović; Thomas P. Vickery; Megan Roth; Daniel J. Muzzio (Process Safety and Environmental Protection, 2023)

Habitat coupling dynamics of mobile consumers along a freshwater and marine resource gradient in a sub-Arctic estuarine system - Jillian R. St George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuarine, Coastal and Shelf Science, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

No evidence of a long-lived seedbank in common buckthorn, Rhamnus cathartica L., within Minnesota deciduous forests - Michael J. Schuster; Peter D. Wragg; Alexander M. Roth; Peter B. Reich (Biological Invasions, 2023)

Distinct fungal and bacterial responses to fire severity and soil depth across a ten-year wildfire chronosequence in beetle-killed lodgepole pine forests - Marcos V. Caiafa; Amelia R. Nelson; Thomas Borch; Holly K. Roth; Timothy S. Fegel; Charles C. Rhoades; Michael J. Wilkins; Sydney I. Glassman (Forest Ecology and Management, 2023)

Evaluation in a porcine wound model and long-term clinical assessment of an autologous heterogeneous skin construct used to close full-thickness wounds - Nicholas Baetz; Pratima Labroo; Marytheresa Ifediba; Devin Miller; Kendall Stauffer; Michael Sieverts; Jessie Nicodemus-Johnson; Eric Chan; Ian Robinson; James Miess; Stephanie Roth; Jenny Irvin; et al. (Tissue and Cell, 2023)

Less is more? A novel method for identifying and evaluating non-informative tracers in sediment source mixing models - Terry Cox; J. Patrick Laceby; Till Roth; Christine Alewell (Journal of Soils and Sediments, 2023)
Purpose Accelerated soil erosion poses a global hazard to soil health. Understanding soil and sediment behaviour through sediment fingerprinting enables the monitoring and identification of areas with high sediment delivery. Land-use specific sediment source apportionment is increasingly determined using the Bayesian mixing model MixSIAR with compound-specific stable isotopes (CSSI). Here, we investigate CSSIs of fatty acid (FA) tracer selection with a novel method to identify and investigate the effect of non-informative tracers on model performance. Methods To evaluate CSSI tracer selection, mathematical mixtures were generated using source soils (n = 28) from the Rhine catchment upstream of Basel (Switzerland). Using the continuous ranked probability (CRP) skill score, MixSIAR’s performance was evaluated for 11 combinations of FAs and 15 combinations of FAs with δ 15 N as a mixing line offset tracer. A novel scaling and discrimination analysis (SDA) was also developed to identify tracers with non-unique mixing spaces. Results FA only tracer combinations overestimated pasture contributions while underestimating arable contributions. When compared to models with only FA tracers, utilizing δ 15 N to offset the mixing line resulted in a 28% improvement in the CRP skill score. δ 15 N + δ 13 C FA 26 was the optimal tracer set resulting in a 62% model improvement relative to δ 15 N + all δ 13 C FAs. The novel SDA method demonstrated how δ 13 C FA tracers have a non-unique mixing space and thus behave as non-informative tracers. Importantly, the inclusion of non-informative tracers decreased model performance. Conclusions These results indicate that MixSIAR did not handle non-informative CSSI tracers effectively. Accordingly, it may be advantageous to remove non-informative tracers, and where feasible, all combinations and permutations of tracers should be assessed to optimize tracer selection. Application of these tracer selection steps can help improve and advance the performance of sediment fingerprinting models and ultimately aid in improving erosion mitigation and management strategies.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

Histochemistry and Cell Biology—a glance into the past and a look ahead - Jürgen Roth; Douglas J. Taatjes (Histochemistry and Cell Biology, 2023)
At the occasion of the 65th anniversary of Histochemistry and Cell Biology , we browse through its first ten years of publication and highlight a selection of papers from the early days of enzyme, protein, and carbohydrate histochemistry. In addition, we narrate recent progress to identify, quantify, and precisely determine the tissue localization of proteins and lipids, and small molecules by the combination of spectroscopic techniques and histology.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

Quantifying the fate of nitrogen from cereal rye root and shoot biomass using 15N - Richard T. Roth; Corey G. Lacey; James J. Camberato; Shalamar D. Armstrong (Nutrient Cycling in Agroecosystems, 2023)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

Multiple sources implicated in the red swamp crayfish invasion in Michigan, USA - N. M. Sard; K. R. Smith; B. M. Roth; L. R. Nathan; S. J. Herbst; K. T. Scribner (Biological Invasions, 2023)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

Experimental natural disturbance-based silviculture systems maintain mature forest bird assemblage long-term in Maine (USA) - Carl K. Pohlman; Amber M. Roth; Mitschka J. Hartley; Malcolm L. Hunter; Brian J. McGill; Robert S. Seymour (Forest Ecology and Management, 2023)

Demonstration of Reversible Dispersion in a Darcy-Scale Push-Pull Laboratory Experiment - Roseanna M. Neupauer; Eric J. Roth; John P. Crimaldi; David C. Mays; Lauren J. Sather (Transport in Porous Media, 2023)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

Editorial - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2023)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

Comparing growth and body condition of wild and hatchery M YY brook trout in streams and alpine lakes - James S. Unsworth; Curtis J. Roth; Kevin A. Meyer (Fisheries Management and Ecology, 2022)
Biologists have theorized that stocking YY males (created via in‐hatchery hormonal sex‐reversal and selective breeding; hereafter M YY fish) could be used to eradicate unwanted non‐native vertebrate populations, but little is known about the fitness of M YY individuals once released into the wild. We compared growth and body condition of stocked hatchery‐reared M YY brook trout ( Salvelinus fontinalis Mitchell) to wild conspecifics in two streams and two alpine lakes. Maximum age for wild fish was age 6 at one stream and age 4 or 5 at the remaining waters, whereas for hatchery M YY fish, maximum age was age 5 at one stream and age 4 at the remaining waters. Total length ranged from 103 to 359 mm for wild brook trout and 115 to 353 mm for hatchery M YY brook trout. Growth rates and body condition of stocked M YY brook trout did not differ from wild fish in the same waters. Given that the success of M YY eradication programs is primarily contingent upon M YY individuals having fitness characteristics similar to wild conspecifics, our results provide further evidence that the stocking of hatchery‐reared M YY fish may be a viable tool for eradicating unwanted non‐native fish populations.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

Targeting Sagebrush (Artemisia Spp.) Restoration Following Wildfire with Greater Sage-Grouse (Centrocercus Urophasianus) Nest Selection and Survival Models - Cali L. Roth; Shawn T. O’Neil; Peter S. Coates; Mark A. Ricca; David A. Pyke; Cameron L. Aldridge; Julie A. Heinrichs; Shawn P. Espinosa; David J. Delehanty (Environmental Management, 2022)
Unprecedented conservation efforts for sagebrush ( Artemisia spp.) ecosystems across the western United States have been catalyzed by risks from escalated wildfire activity that reduces habitat for sagebrush-obligate species such as Greater Sage-Grouse ( Centrocercus urophasianus ). However, post-fire restoration is challenged by spatial variation in ecosystem processes influencing resilience to disturbance and resistance to non-native invasive species, and spatial and temporal lags between slower sagebrush recovery processes and faster demographic responses of sage-grouse to loss of important habitat. Decision-support frameworks that account for these factors can help users strategically apply restoration efforts by predicting short and long-term ecological benefits of actions. Here, we developed a framework that strategically targets burned areas for restoration actions (e.g., seeding or planting sagebrush) that have the greatest potential to positively benefit sage-grouse populations through time. Specifically, we estimated sagebrush recovery following wildfire and risk of non-native annual grass invasion under four scenarios: passive recovery, grazing exclusion, active restoration with seeding, and active restoration with seedling transplants. We then applied spatial predictions of integrated nest site selection and survival models before wildfire, immediately following wildfire, and at 30 and 50 years post-wildfire based on each restoration scenario and measured changes in habitat. Application of this framework coupled with strategic planting designs aimed at developing patches of nesting habitat may help increase operational resilience for fire-impacted sagebrush ecosystems.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

Lean mass sparing in resistance-trained athletes during caloric restriction: the role of resistance training volume - C. Roth; B. J. Schoenfeld; M. Behringer (European Journal of Applied Physiology, 2022)
Many sports employ caloric restriction (CR) to reduce athletes’ body mass. During these phases, resistance training (RT) volume is often reduced to accommodate recovery demands. Since RT volume is a well-known anabolic stimulus, this review investigates whether a higher training volume helps to spare lean mass during CR. A total of 15 studies met inclusion criteria. The extracted data allowed calculation of total tonnage lifted (repetitions × sets × intensity load) or weekly sets per muscle group for only 4 of the 15 studies, with RT volume being highly dependent on the examined muscle group as well as weekly training frequency per muscle group. Studies involving high RT volume programs (≥ 10 weekly sets per muscle group) revealed low-to-no (mostly female) lean mass loss. Additionally, studies increasing RT volume during CR over time appeared to demonstrate no-to-low lean mass loss when compared to studies reducing RT volume. Since data regarding RT variables applied were incomplete in most of the included studies, evidence is insufficient to conclude that a higher RT volume is better suited to spare lean mass during CR, although data seem to favor higher volumes in female athletes during CR. Moreover, the data appear to suggest that increasing RT volume during CR over time might be more effective in ameliorating CR-induced atrophy in both male and female resistance-trained athletes when compared to studies reducing RT volume. The effects of CR on lean mass sparing seem to be mediated by training experience, pre-diet volume, and energy deficit, with, on average, women tending to spare more lean mass than men. Potential explanatory mechanisms for enhanced lean mass sparing include a preserved endocrine milieu as well as heightened anabolic signaling.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

Correction to: In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

Combined effects of heatwaves and micropollutants on freshwater ecosystems: Towards an integrated assessment of extreme events in multiple stressors research - Francesco Polazzo; Sabrina K. Roth; Markus Hermann; Annika Mangold‐Döring; Andreu Rico; Anna Sobek; Paul J. Van den Brink; Michelle C. Jackson (Global Change Biology, 2022)
Freshwater ecosystems are strongly influenced by weather extremes such as heatwaves (HWs), which are predicted to increase in frequency and magnitude in the future. In addition to these climate extremes, the freshwater realm is impacted by the exposure to various classes of chemicals emitted by anthropogenic activities. Currently, there is limited knowledge on how the combined exposure to HWs and chemicals affects the structure and functioning of freshwater ecosystems. Here, we review the available literature describing the single and combined effects of HWs and chemicals on different levels of biological organization, to obtain a holistic view of their potential interactive effects. We only found a few studies (13 out of the 61 studies included in this review) that investigated the biological effects of HWs in combination with chemical pollution. The reported interactive effects of HWs and chemicals varied largely not only within the different trophic levels but also depending on the studied endpoints for populations or individuals. Hence, owing also to the little number of studies available, no consistent interactive effects could be highlighted at any level of biological organization. Moreover, we found an imbalance towards single species and population experiments, with only five studies using a multitrophic approach. This results in a knowledge gap for relevant community and ecosystem level endpoints, which prevents the exploration of important indirect effects that can compromise food web stability. Moreover, this knowledge gap impairs the validity of chemical risk assessments and our ability to protect ecosystems. Finally, we highlight the urgency of integrating extreme events into multiple stressors studies and provide specific recommendations to guide further experimental research in this regard.

Neuroinflammation in Primary Cultures of the Rat Spinal Dorsal Horn Is Attenuated in the Presence of Adipose Tissue–Derived Medicinal Signalling Cells (AdMSCs) in a Co-cultivation Model - Stephan Leisengang; Laura B. Heilen; Michele C. Klymiuk; Franz Nürnberger; Daniela Ott; Kathrin Wolf-Hofmann; Rüdiger Gerstberger; Christoph Rummel; Martin J. Schmidt; Stefan Arnhold; Joachim Roth (Molecular Neurobiology, 2022)
Neuroinflammation within the superficial dorsal horn (SDH) of the spinal cord induces inflammatory pain with symptoms of hyperalgesia and allodynia. Glial activation and production of inflammatory mediators (e.g. cytokines) is associated with modulation of nociceptive signalling. In this context, medicinal signalling cells, e.g. obtained from adipose tissue (AdMSCs), gained attention due to their capacity to modulate the inflammatory response in several diseases, e.g. spinal cord injury. We applied the recently established mixed neuroglial primary cell culture of the rat SDH to investigate effects of AdMSCs on the inflammatory response of SDH cells. Following establishment of a co-cultivation system, we performed specific bioassays for tumour necrosis factor alpha (TNFα) and interleukin (IL)-6, RT-qPCR and immunocytochemistry to detect changes in cytokine production and glial activation upon inflammatory stimulation with lipopolysaccharide (LPS). LPS-induced expression and release of pro-inflammatory cytokines (TNFα, IL-6) by SDH cells was significantly attenuated in the presence of AdMSCs. Further evidence for anti-inflammatory capacities of AdMSCs derived from a blunted LPS-induced TNFα/IL-10 expression ratio and suppressed nuclear translocation of the inflammatory transcription factor nuclear factor kappa B (NFκB) in SDH microglial cells. Expression of IL-10, transforming growth factor beta (TGF-β) and TNFα-stimulated gene-6 (TSG-6) was detected in AdMSCs, which are putative candidates for anti-inflammatory capacities of these cells. We present a novel co-cultivation system of AdMSCs with neuroglial primary cultures of the SDH to investigate immunomodulatory effects of AdMSCs at a cellular level.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2022)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

Enhanced error facilitates motor learning in weight shift and increases use of the paretic leg during walking at chronic stage after stroke - Seoung Hoon Park; Chao-Jung Hsu; Weena Dee; Elliot J. Roth; William Z. Rymer; Ming Wu (Experimental Brain Research, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

Type of broadleaf forest matters most for ptyctimous mite communities (Acari, Oribatida) in Norway - Anna Seniczak; Wojciech Niedbała; J. Carlos Iturrondobeitia; Stanisław Seniczak; Steffen Roth; Bjarte H. Jordal (Biodiversity and Conservation, 2021)
We studied ptyctimous moss mites, which are characteristic of forest habitats, in Norwegian broadleaf forests considered as biodiversity hotspot areas in Fennoscandia. The study aimed to evaluate the effect of different factors (regional locality, annual precipitation, mean annual temperature, forest type, forest wetness and microhabitat) on the ptyctimous mites and on discovering their richness in broadleaf forests. Samples were collected from nine broadleaf forests in Western, Southern and Eastern Norway, in different climatic conditions, six forest types, three forest wetness states and eight microhabitats. Overall, 3341 ptyctimous mites were collected and their abundance differed significantly among the regions, forest types and microhabitats. Forest type turned out to be the most important factor, responsible for 24.5% of the total variation in the abundance of the ptyctimous mites. Other important factors were forest wetness and microhabitat. In total, 27 species, i.e., 87% of all ptyctimous mites known from before in Norway were found and the species richness was highest in the east and lowest in the west of the country. Atropacarus (Atropacarus) striculus was most common and most abundant; it made nearly 30% of all ptyctimous mites collected. On the other hand, a quarter of the species were represented by less than 10 specimens; most of these were new records for Norway. Among ten species discovered as new to Norway, four were also new to Fennoscandia. These findings confirm the unique character and high biological diversity of Norwegian broadleaf forests.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

Gradual adaptation to pelvis perturbation during walking reinforces motor learning of weight shift toward the paretic side in individuals post-stroke - Seoung Hoon Park; Chao-Jung Hsu; Weena Dee; Elliot J. Roth; William Z. Rymer; Ming Wu (Experimental Brain Research, 2021)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

Dynamic macromolecular composition and high exudation rates in Prochlorococcus - Dalit Roth‐Rosenberg; Dikla Aharonovich; Anne Willem Omta; Michael J. Follows; Daniel Sher (Limnology and Oceanography, 2021)
Every living cell is composed of macromolecules such as proteins, DNA, RNA, and pigments. The ratio between these macromolecular pools depends on the allocation of resources within the organism to different physiological requirements, and in turn affects biogeochemical cycles of elements such as carbon, nitrogen, and phosphorus. Here, we present detailed measurements of the macromolecular composition of Prochlorococcus MIT9312, a representative strain of a globally abundant marine primary producer, as it grows and declines due to nitrogen starvation in laboratory batch cultures. As cells reached stationary stage and declined, protein per cell decreased by ~ 30% whereas RNA per cell and pigments per cell decreased by ~ 75%. The decline stage was associated with the appearance of chlorotic cells, which had higher forward scatter (a proxy for cell size) but lower chlorophyll autofluorescence, as well as with changes in photosynthetic pigment composition. Specifically, during culture decline divinyl‐chlorophyll‐like pigments emerged, which were not observed during exponential growth. These divinyl‐chlorophyll‐like pigments were also observed in natural samples from the Eastern Mediterranean. Over 90% of the carbon fixed by Prochlorococcus MIT9312 (but not of a different strain, NATL2A) was released into the growth media under these laboratory conditions. Variations in RNA/protein indicate that, broadly defined, the macromolecular composition of Prochlorococcus MIT9312 is more similar to eukaryotic phytoplankton than to marine heterotrophic bacteria, possibly due to the significant investment in photosynthetic machinery of phototrophs.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

Methods for Laser-Induced Fluorescence Imaging of Solute Plumes at the Darcy Scale in Quasi-Two-Dimensional, Refractive Index-Matched Porous Media - Eric J. Roth; David C. Mays; Roseanna M. Neupauer; Lauren J. Sather; John P. Crimaldi (Transport in Porous Media, 2021)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2021)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

Wall Effect Mitigation Techniques for Experiments with Planar Walls - Eric J. Roth; Roseanna M. Neupauer; David C. Mays; Lauren J. Sather; John P. Crimaldi (Transport in Porous Media, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2020)

Irritable Bowel Syndrome, Immune Fitness, and Insomnia: Results from an Online Survey Among People Reporting Sleep Complaints - Smedra Abdulahad; Hendrikje Huls; Stephanie Balikji; Aurora J. A. E. van de Loo; Thomas Roth; Joris C. Verster (Sleep and Vigilance, 2019)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

Multiple stressor effects on coral reef ecosystems - Joanne I. Ellis; Tahira Jamil; Holger Anlauf; Darren J. Coker; Joao Curdia; Judi Hewitt; Burton H. Jones; George Krokos; Benjamin Kürten; Dasari Hariprasad; Florian Roth; Susana Carvalho; et al. (Global Change Biology, 2019)
Global climate change has profound implications on species distributions and ecosystem functioning. In the coastal zone, ecological responses may be driven by various biogeochemical and physical environmental factors. Synergistic interactions can occur when the combined effects of stressors exceed their individual effects. The Red Sea, characterized by strong gradients in temperature, salinity, and nutrients along the latitudinal axis provides a unique opportunity to study ecological responses over a range of these environmental variables. Using multiple linear regression models integrating in situ, satellite and oceanographic data, we investigated the response of coral reef taxa to local stressors and recent climate variability. Taxa and functional groups responded to a combination of climate (temperature, salinity, air‐sea heat fluxes, irradiance, wind speed), fishing pressure and biogeochemical (chlorophyll a and nutrients ‐ phosphate, nitrate, nitrite) factors. The regression model for each species showed interactive effects of climate, fishing pressure and nutrient variables. The nature of the effects (antagonistic or synergistic) was dependent on the species and stressor pair. Variables consistently associated with the highest number of synergistic interactions included heat flux terms, temperature, and wind speed followed by fishing pressure. Hard corals and coralline algae abundance were sensitive to changing environmental conditions where synergistic interactions decreased their percentage cover. These synergistic interactions suggest that the negative effects of fishing pressure and eutrophication may exacerbate the impact of climate change on corals. A high number of interactions were also recorded for algae, however for this group, synergistic interactions increased algal abundance. This study is unique in applying regression analysis to multiple environmental variables simultaneously to understand stressor interactions in the field. The observed responses have important implications for understanding climate change impacts on marine ecosystems and whether managing local stressors, such as nutrient enrichment and fishing activities, may help mitigate global drivers of change.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

Comparing temperature data sources for use in species distribution models: From in‐situ logging to remote sensing - Jonas J. Lembrechts; Jonathan Lenoir; Nina Roth; Tarek Hattab; Ann Milbau; Sylvia Haider; Loïc Pellissier; Aníbal Pauchard; Amanda Ratier Backes; Romina D. Dimarco; Martin A. Nuñez; Juha Aalto; et al. (Global Ecology and Biogeography, 2019)
Aim Although species distribution models (SDMs) traditionally link species occurrences to free‐air temperature data at coarse spatio‐temporal resolution, the distribution of organisms might instead be driven by temperatures more proximal to their habitats. Several solutions are currently available, such as downscaled or interpolated coarse‐grained free‐air temperatures, satellite‐measured land surface temperatures (LST) or in‐situ‐measured soil temperatures. A comprehensive comparison of temperature data sources and their performance in SDMs is, however, currently lacking. Location Northern Scandinavia. Time period 1970–2017. Major taxa studied Higher plants. Methods We evaluated different sources of temperature data (WorldClim, CHELSA, MODIS, E‐OBS, topoclimate and soil temperature from miniature data loggers), differing in spatial resolution (from 1″ to 0.1°), measurement focus (free‐air, ground‐surface or soil temperature) and temporal extent (year‐long versus long‐term averages), and used them to fit SDMs for 50 plant species with different growth forms in a high‐latitudinal mountain region. Results Differences between these temperature data sources originating from measurement focus and temporal extent overshadow the effects of temporal climatic differences and spatio‐temporal resolution, with elevational lapse rates ranging from −0.6°C per 100 m for long‐term free‐air temperature data to −0.2°C per 100 m for in‐situ soil temperatures. Most importantly, we found that the performance of the temperature data in SDMs depended on the growth forms of species. The use of in‐situ soil temperatures improved the explanatory power of our SDMs ( R 2 on average +16%), especially for forbs and graminoids ( R 2 +24 and +21% on average, respectively) compared with the other data sources. Main conclusions We suggest that future studies using SDMs should use the temperature dataset that best reflects the ecology of the species, rather than automatically using coarse‐grained data from WorldClim or CHELSA.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

Ecophysiology of mesophotic reef‐building corals in Hawai‘i is influenced by symbiont–host associations, photoacclimatization, trophic plasticity, and adaptation - Jacqueline L. Padilla‐Gamiño; Melissa S. Roth; Lisa J. Rodrigues; Christina J. Bradley; Robert R. Bidigare; Ruth D. Gates; Celia M. Smith; Heather L. Spalding (Limnology and Oceanography, 2019)
Mesophotic reef corals remain largely unexplored in terms of the genetic adaptations and physiological mechanisms to acquire, allocate, and use energy for survival and reproduction. In the Hawaiian Archipelago, the Leptoseris species complex form the most spatially extensive mesophotic coral ecosystem known and provide habitat for a unique community. To study how the ecophysiology of Leptoseris species relates to symbiont–host specialization and understand the mechanisms responsible for coral energy acquisition in extreme low light environments, we examined Symbiodinium (endosymbiotic dinoflagellate) photobiological characteristics and the lipids and isotopic signatures from Symbiodinium and coral hosts over a depth‐dependent light gradient (55–7 μ mol photons m −2 s −1 , 60–132 m). Clear performance differences demonstrate different photoadaptation and photoacclimatization across this genus. Our results also show that flexibility in photoacclimatization depends primarily on Symbiodinium type. Colonies harboring Symbiodinium sp. COI‐2 showed significant increases in photosynthetic pigment content with increasing depth, whereas colonies harboring Symbiodinium spp. COI‐1 and COI‐3 showed variability in pigment composition, yield measurements for photosystem II, as well as size and density of Symbiodinium cells. Despite remarkable differences in photosynthetic adaptive strategies, there were no significant differences among lipids of Leptoseris species with depth. Finally, isotopic signatures of both host and Symbiodinium changed with depth, indicating that coral colonies acquired energy from different sources depending on depth. This study highlights the complexity in physiological adaptations within this symbiosis and the different strategies used by closely related mesophotic species to diversify energy acquisition and to successfully establish and compete in extreme light‐limited environments.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

Histochemistry and Cell Biology: 61 years and not tired at all - Douglas J. Taatjes; Michael Schrader; Takehiko Koji; Jürgen Roth (Histochemistry and Cell Biology, 2019)

In Focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

Constraints to the capacity of smallholder farming households to adapt to climate change in South and Southeast Asia - Peter R. Brown; Sharmin Afroz; Lytoua Chialue; T. Chiranjeevi; Sotheary El; Clemens M. Grünbühel; Iqbal Khan; Cathy Pitkin; V. Ratna Reddy; Christian H. Roth; Silinthone Sacklokham; Liana J. Williams (Climate and Development, 2019)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

Enhanced detection and estimation of regional S-phases using the 3-component ARCES array - Steven J. Gibbons; Johannes Schweitzer; Tormod Kværna; Michael Roth (Journal of Seismology, 2019)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

Changes in the distribution of Michigan crayfishes and the influence of invasive rusty crayfish (Faxonius rusticus) on native crayfish substrate associations - Kelley R. Smith; Brian M. Roth; Michael L. Jones; Daniel B. Hayes; Seth J. Herbst; Nicholas Popoff (Biological Invasions, 2019)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2019)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

Iron-Based Metal-Organic Frameworks as a Theranostic Carrier for Local Tuberculosis Therapy - Gabriela Wyszogrodzka; Przemysław Dorożyński; Barbara Gil; Wieslaw J. Roth; Maciej Strzempek; Bartosz Marszałek; Władysław P. Węglarz; Elżbieta Menaszek; Weronika Strzempek; Piotr Kulinowski (Pharmaceutical Research, 2018)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

Sex Differences in Early Postnatal Microglial Colonization of the Developing Rat Hippocampus Following a Single-Day Alcohol Exposure - M. J. Ruggiero; K. E. Boschen; T. L. Roth; A. Y. Klintsova (Journal of Neuroimmune Pharmacology, 2018)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

Functional biogeography and host specificity of bacterial communities associated with the Marine Green Alga Ulva spp. - Alexandra J. Roth‐Schulze; José Pintado; Enrique Zozaya‐Valdés; Javier Cremades; Patricia Ruiz; Staffan Kjelleberg; Torsten Thomas (Molecular Ecology, 2018)
Bacterial communities play an essential role for the function of marine macroalgae. Recent work has shown that bacterial communities associated with individual macroalgae possess on a local scale a functional core that is likely derived from diverse members of functional guilds. It is not known whether such functional cores also exist across large spatial scales or between closely related host species. To address this, we studied here the bacterial communities on three species of the green macroalgal genus Ulva from different geographic locations. While the taxonomic composition was too variable to describe a community core, we identified genes that were enriched across all Ulva samples as compared to the communities of the surrounding seawater. Of these core functions, 70% were consistently found and independent of the Ulva species and biogeography, while the remaining functions (~30%) are possibly involved in local or host‐specific adaptations. For each host individual, the core functions are provided by bacteria with distinct phylogenetic origin and these bacteria could constitute a global guild of Ulva ‐associated bacteria. Together, our results demonstrate the presence of a stable core set of functional genes in the bacterial communities associated with closely related host species and across large biogeographies.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

The effects of warming and ocean acidification on growth, photosynthesis, and bacterial communities for the marine invasive macroalga Caulerpa taxifolia - Alexandra J. Roth‐Schulze; Torsten Thomas; Peter Steinberg; Marty R. Deveney; Jason E. Tanner; Kathryn H. Wiltshire; Stephanie Papantoniou; John W. Runcie; C. Frederico D. Gurgel (Limnology and Oceanography, 2018)
Caulerpa taxifolia is a pantropical green benthic marine macroalga, and one of the best known marine invasive species in temperate coastal habitats. In Australia, this species has been introduced to seven estuaries along New South Wales and one in South Australia. How this alga will perform under future climate change scenarios is however not well defined. This study experimentally assessed the effects of ocean acidification and global warming on the growth, photosynthetic performance and the bacterial community on two populations of C. taxifolia , one native and one invasive. A range of complex significant interactive effects between pH, temperature, and initial plant size on the growth of C. taxifolia were observed, but no effect of population origin and photosystem II (PSII) fluorescence quantum yield parameters were detected. No significant effects of the treatment combinations were observed on bacterial community richness or diversity. Only one bacterial species out of 1087 present on the algae showed significant changes between pH treatments at high temperature (24°C). This bacterium belonged to the genus Planctomyces and its relative abundance was more than 10 times higher in samples with low pH compared to the control. Higher plant growth was observed under all higher pCO 2 and lower pH conditions suggesting that C. taxifolia will benefit from climate change, posing a potential higher risk in invaded locations.

The Impact of Having a 15-min Break With and Without Consuming an Energy Drink on Prolonged Simulated Highway Driving - Joris C. Verster; Aurora J. A. E. van de Loo; Adriana C. Bervoets; Loes Mooren; Thomas Roth (Sleep and Vigilance, 2017)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

A neutron diffraction study of crystal and low-temperature magnetic structures within the (Na,Li)FeGe2O6 pyroxene-type solid solution series - Günther J. Redhammer; Anatoliy Senyshyn; Stefan Lebernegg; Gerold Tippelt; Edgar Dachs; Georg Roth (Physics and Chemistry of Minerals, 2017)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

Quantitative biogeography of picoprasinophytes establishes ecotype distributions and significant contributions to marine phytoplankton - Alexander J. Limardo; Sebastian Sudek; Chang Jae Choi; Camille Poirier; Yoshimi M. Rii; Marguerite Blum; Robyn Roth; Ursula Goodenough; Matthew J. Church; Alexandra Z. Worden (Environmental Microbiology, 2017)
Summary Bathycoccus and Ostreococcus are broadly distributed marine picoprasinophyte algae. We enumerated small phytoplankton using flow cytometry and qPCR assays for phylogenetically distinct Bathycoccus clades BI and BII and Ostreococcus clades OI and OII. Among 259 photic‐zone samples from transects and time‐series, Ostreococcus maxima occurred in the North Pacific coastal upwelling for OI (36 713 ± 1485 copies ml −1 ) and the Kuroshio Front for OII (50 189 ± 561 copies ml −1 ) and the two overlapped only in frontal regions. The Bathycoccus overlapped more often with maxima along Line‐P for BI (10 667 ± 1299 copies ml −1 ) and the tropical Atlantic for BII (4125 ± 339 copies ml −1 ). Only BII and OII were detected at warm oligotrophic sites, accounting for 34 ± 13% of 1589 ± 448 eukaryotic phytoplankton cells ml −1 (annual average) at Station ALOHA's deep chlorophyll maximum. Significant distributional and molecular differences lead us to propose that Bathycoccus clade BII represents a separate species which tolerates higher temperature oceanic conditions than Bathycoccus prasinos (BI). Morphological differences were not evident, but quick‐freeze deep‐etch electron microscopy provided insight into Bathycoccus scale formation. Our results highlight the importance of quantitative seasonal abundance data for inferring ecological distributions and demonstrate significant, differential picoprasinophyte contributions in mesotrophic and open‐ocean waters.

Microbial community function in the bleaching disease of the marine macroalgae Delisea pulchra - Enrique Zozaya‐Valdés; Alexandra J. Roth‐Schulze; Suhelen Egan; Torsten Thomas (Environmental Microbiology, 2017)
Summary Disease is increasingly viewed as a major factor impacting the health of both natural and cultured populations of marine organisms, including macroalgae. The red macroalga Delisea pulchra suffers from a bleaching disease resulting from host stress and infection by opportunistic bacterial pathogens. However, how pathogens cause the disease and how the entire macro algal‐associated community is involved in the process is unclear. Here, we perform a metagenomic analysis of microbial communities associated with diseased and healthy D. pulchra across multiple bleaching events. Analysis of reconstructed 16S rRNA gene sequences showed that bacteria belonging to the families Rhodobacteraceae , Saprospiraceae and Flavobacteriaceae , including bacteria previously implicated in algal bleaching, to be enriched in diseased D. pulchra . Genes with predicted functions related to chemotaxis, motility, oxidative stress response, vitamin biosynthesis and nutrient acquisition were also prevalent in microbiomes of bleached algae, which may have a role in pathogenicity. Reconstruction of genomes that were abundant on bleached samples revealed that no single organism contains all bleaching‐enriched functional genes. This observation indicates that potential virulence traits are distributed across multiple bacteria and that the disease in D. pulchra may result from a consortium of opportunistic pathogens, analogous to dysbiotic or polymicrobial diseases.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

Prochlorococcus in the lab and in silico: The importance of representing exudation - Michal Grossowicz; Dalit Roth‐Rosenberg; Dikla Aharonovich; Jacob Silverman; Michael J. Follows; Daniel Sher (Limnology and Oceanography, 2017)
In this study, we test the applicability of the Droop/Caperon internal stores model to describe the growth and decline of the globally abundant marine cyanobacterium Prochlorococcus in batch culture as a function of internal and external inorganic and organic carbon and nitrogen. A rigorous parameter fitting exercise, constrained by the measured cell density, ammonium and inorganic carbon concentrations, revealed many different combinations of parameter values that provided equally good model‐data fit. Introducing data on C : N ratio from the published literature provided additional constraints which could only be satisfied with a structural change to the model. The simplest addition that satisfied these constraints and improved quantitative overall model‐data agreement was to explicitly represent excretion, which was predicted to account for 0.03–8.5% of the daily primary productivity; somewhat lower than previous estimates based on radiotracer incorporation. We argue that this significant and biologically meaningful process should not be neglected in models of marine phytoplankton.

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2017)

Partitioning of functional and taxonomic diversity in surface‐associated microbial communities - Alexandra J. Roth‐Schulze; Enrique Zozaya‐Valdés; Peter D. Steinberg; Torsten Thomas (Environmental Microbiology, 2016)
Summary Surfaces, including those submerged in the marine environment, are subjected to constant interactions and colonisation by surrounding microorganisms. The principles that determine the assembly of those epibiotic communities are however poorly understood. In this study, we employed a hierarchical design to assess the functionality and diversity of microbial communities on different types of host surfaces (e.g. macroalgae, seagrasses). We found that taxonomic diversity was unique to each type of host, but that the majority of functions (> 95%) could be found in any given surface community, suggesting a high degree of functional redundancy. However, some community functions were enriched on certain surfaces and were related to host‐specific properties (e.g. the degradation of specific polysaccharides). Together these observations support a model, whereby communities on surfaces are assembled from guilds of microorganisms with a functionality that is partitioned into general properties for a surface‐associated life‐style, but also specific features that mediate host‐specificity.

In focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2016)

Household types as a tool to understand adaptive capacity: case studies from Cambodia, Lao PDR, Bangladesh and India - Liana J. Williams; Sharmin Afroz; Peter R. Brown; Lytoua Chialue; Clemens M. Grünbühel; Tanya Jakimow; Iqbal Khan; Mao Minea; V. Ratna Reddy; Silinthone Sacklokham; Emmanuel Santoyo Rio; Mak Soeun; et al. (Climate and Development, 2016)

In Focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2016)

In Focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2016)

In Focus in HCB - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2016)

The Histochemistry and Cell Biology omnium-gatherum: the year 2015 in review - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2016)

Siderophore production by streptomycetes—stability and alteration of ferrihydroxamates in heavy metal-contaminated soil - Eileen Schütze; Engy Ahmed; Annekatrin Voit; Michael Klose; Matthias Greyer; Aleš Svatoš; Dirk Merten; Martin Roth; Sara J. M. Holmström; Erika Kothe (Environmental Science and Pollution Research, 2015)

Effect of manganese treatment on the accumulation on biologically relevant metals in rat cochlea and brain by inductively coupled plasma mass spectrometry - Elizabeth J. Mullin; Stacia R. Wegst-Uhrich; Dalian Ding; Senthilvelan Manohar; Vijaya Prakash Krishnan Muthaiah; Richard Salvi; Diana S. Aga; Jerome A. Roth (BioMetals, 2015)

Structural and magnetic phase transitions in the synthetic clinopyroxene LiCrGe2O6: a neutron diffraction study between 0.5 and 1473 K - Günther J. Redhammer; Anatoliy Senyshyn; Gerold Tippelt; Sebastian Prinz; Georg Roth (Physics and Chemistry of Minerals, 2015)

Invasive earthworms interact with abiotic conditions to influence the invasion of common buckthorn (Rhamnus cathartica) - Alexander M. Roth; Timothy J. S. Whitfeld; Alexandra G. Lodge; Nico Eisenhauer; Lee E. Frelich; Peter B. Reich (Oecologia, 2015)

The Histochemistry and Cell Biology pandect: the year 2014 in review - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2015)

A whole-lake experiment to control invasive rainbow smelt (Actinoperygii, Osmeridae) via overharvest and a food web manipulation - Jereme W. Gaeta; Thomas R. Hrabik; Greg G. Sass; Brian M. Roth; Stephen J. Gilbert; M. Jake Vander Zanden (Hydrobiologia, 2015)

Endogenous concentrations of biologically relevant metals in rat brain and cochlea determined by inductively coupled plasma mass spectrometry - Stacia R. Wegst-Uhrich; Elizabeth J. Mullin; Dalian Ding; Senthilvelan Manohar; Richard Salvi; Diana S. Aga; Jerome A. Roth (BioMetals, 2015)

Genome and physiology of the ascomycete filamentous fungus X eromyces bisporus , the most xerophilic organism isolated to date - Su‐lin L. Leong; Henrik Lantz; Olga V. Pettersson; Jens C. Frisvad; Ulf Thrane; Hermann J. Heipieper; Jan Dijksterhuis; Manfred Grabherr; Mats Pettersson; Christian Tellgren‐Roth; Johan Schnürer (Environmental Microbiology, 2015)
Summary X eromyces bisporus can grow on sugary substrates down to 0.61, an extremely low water activity. Its genome size is approximately 22 Mb . Gene clusters encoding for secondary metabolites were conspicuously absent; secondary metabolites were not detected experimentally. Thus, in its ‘dry’ but nutrient‐rich environment, X . bisporus appears to have relinquished abilities for combative interactions. Elements to sense/signal osmotic stress, e.g. HogA pathway, were present in X . bisporus . However, transcriptomes at optimal (∼ 0.89) versus low a w (0.68) revealed differential expression of only a few stress‐related genes; among these, certain (not all) steps for glycerol synthesis were upregulated. X eromyces bisporus increased glycerol production during hypo‐ and hyper‐osmotic stress, and much of its wet weight comprised water and rinsable solutes; leaked solutes may form a protective slime. X eromyces bisporus and other food‐borne moulds increased membrane fatty acid saturation as water activity decreased. Such modifications did not appear to be transcriptionally regulated in X . bisporus ; however, genes modulating sterols, phospholipids and the cell wall were differentially expressed. X eromyces bisporus was previously proposed to be a ‘chaophile’, preferring solutes that disorder biomolecular structures. Both X . bisporus and the closely related xerophile, X erochrysium xerophilum , with low membrane unsaturation indices, could represent a phylogenetic cluster of ‘chaophiles’.

The opioid receptor pharmacology of GSK1521498 compared to other ligands with differential effects on compulsive reward-related behaviours - Eamonn Kelly; Stuart J. Mundell; Anna Sava; Adelheid L. Roth; Antonio Felici; Kay Maltby; Pradeep J. Nathan; Edward T. Bullmore; Graeme Henderson (Psychopharmacology, 2015)

Resident plant diversity and introduced earthworms have contrasting effects on the success of invasive plants - Timothy J. S. Whitfeld; Alexander M. Roth; Alexandra G. Lodge; Nico Eisenhauer; Lee E. Frelich; Peter B. Reich (Biological Invasions, 2014)

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

The movement of a nerve in a magnetic field: application to MRI Lorentz effect imaging - Bradley J. Roth; Adam Luterek; Steffan Puwal (Medical & Biological Engineering & Computing, 2014)

The Histochem Cell Biol conspectus: the year 2013 in review - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2014)

A Simplified Approach for Simultaneous Measurements of Wavefront Velocity and Curvature in the Heart Using Activation Times - Nachaat Mazeh; David E. Haines; Matthew W. Kay; Bradley J. Roth (Cardiovascular Engineering and Technology, 2013)

Slaughter of Atlantic salmon (Salmo salar L.) in the presence of carbon monoxide - Gry Aletta Bjørlykke; Bjørn Olav Kvamme; Arnt J. Raae; Bjorn Roth; Erik Slinde (Fish Physiology and Biochemistry, 2013)

Assessment of Juvenile Pigs to Serve as Human Pediatric Surrogates for Preclinical Formulation Pharmacokinetic Testing - Wyatt J. Roth; Candice B. Kissinger; Robyn R. McCain; Bruce R. Cooper; Jeremy N. Marchant-Forde; Rachel C. Vreeman; Sophia Hannou; Gregory T. Knipp (The AAPS Journal, 2013)

The Histochemistry and Cell Biology compendium: a review of 2012 - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2013)

Are all eggs created equal? A case study from the Hawaiian reef-building coral Montipora capitata - Jacqueline L. Padilla-Gamiño; Robert R. Bidigare; Daniel J. Barshis; Ada Alamaru; Laetitia Hédouin; Xavier Hernández-Pech; Frederique Kandel; Sherril Leon Soon; Melissa S. Roth; Lisa J. Rodrigues; Andrea G. Grottoli; Claudia Portocarrero; et al. (Coral Reefs, 2013)

How Effective is Reduced Tillage–Cover Crop Management in Reducing N2O Fluxes from Arable Crop Soils? - M. Abdalla; K. Rueangritsarakul; M. Jones; B. Osborne; M. Helmy; B. Roth; J. Burke; P. Nolan; P. Smith; M. Williams (Water, Air, & Soil Pollution, 2012)

Population genetic structure and its implications for adaptive variation in memory and the hippocampus on a continental scale in food‐caching black‐capped chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; T. M. Burg; M. J. Braun; B. S. Davidson (Molecular Ecology, 2012)
Food‐caching birds rely on stored food to survive the winter, and spatial memory has been shown to be critical in successful cache recovery. Both spatial memory and the hippocampus, an area of the brain involved in spatial memory, exhibit significant geographic variation linked to climate‐based environmental harshness and the potential reliance on food caches for survival. Such geographic variation has been suggested to have a heritable basis associated with differential selection. Here, we ask whether population genetic differentiation and potential isolation among multiple populations of food‐caching black‐capped chickadees is associated with differences in memory and hippocampal morphology by exploring population genetic structure within and among groups of populations that are divergent to different degrees in hippocampal morphology. Using mitochondrial DNA and 583 AFLP loci, we found that population divergence in hippocampal morphology is not significantly associated with neutral genetic divergence or geographic distance, but instead is significantly associated with differences in winter climate. These results are consistent with variation in a history of natural selection on memory and hippocampal morphology that creates and maintains differences in these traits regardless of population genetic structure and likely associated gene flow.

Isoform specific regulation of divalent metal (ion) transporter (DMT1) by proteasomal degradation - Michael D. Garrick; Lin Zhao; Jerome A. Roth; Houbo Jiang; Jian Feng; Natalie J. Foot; Hazel Dalton; Sharad Kumar; Laura M. Garrick (BioMetals, 2012)

Is it possible to detect dendrite currents using presently available magnetic resonance imaging techniques? - William I. Jay; Ranjith S. Wijesinghe; Brain D. Dolasinski; Bradley J. Roth (Medical & Biological Engineering & Computing, 2012)

Comparison of the novel ResPlex III assay and existing techniques for the detection and subtyping of influenza virus during the influenza season 2006–2007 - M. Eggers; B. Roth; B. Schweiger; M. Schmid; J.-P. Gregersen; M. Enders (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Does insulin-like growth factor 1 genotype influence muscle power response to strength training in older men and women? - Suchi Sood; Erik D. Hanson; Matthew J. Delmonico; Matthew C. Kostek; Brian D. Hand; Stephen M. Roth; Ben F. Hurley (European Journal of Applied Physiology, 2012)

The ommatidia of Arca noae: a three-tier structure with a central light-guiding element for the receptor cell - Jürgen Roth; Bruno Guhl; Urs Kloter; Walter J. Gehring (Histochemistry and Cell Biology, 2011)

Porous EH and EH-PEG Scaffolds as Gene Delivery Vehicles to Skeletal Muscle - Erin E. Falco; Martha O. Wang; Joshua A. Thompson; Joshua M. Chetta; Diana M. Yoon; Erik Z. Li; Mangesh M. Kulkami; Sameer Shah; Abhay Pandit; J. Scott Roth; John P. Fisher (Pharmaceutical Research, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Nuclear and incommensurate magnetic structure of NaFeGe2O6 between 5 K and 298 K and new data on multiferroic NaFeSi2O6 - Günther J. Redhammer; Anatoliy Senyshyn; Martin Meven; Georg Roth; Sebastian Prinz; Astrid Pachler; Gerold Tippelt; Clemens Pietzonka; Werner Treutmann; Markus Hoelzel; Björn Pedersen; Georg Amthauer (Physics and Chemistry of Minerals, 2011)

ICUC‐7 Urban Climate Special Issue - M. Roth; R. Emmanuel; T. Ichinose; J. Salmond (International Journal of Climatology, 2011)

Thermal expansion and high-temperature P21/c–C2/c phase transition in clinopyroxene-type LiFeGe2O6 and comparison to NaFe(Si,Ge)2O6 - Günther J. Redhammer; Fernando Cámara; Matteo Alvaro; Fabrizio Nestola; Gerold Tippelt; Sebastian Prinz; Jan Simons; Georg Roth; Georg Amthauer (Physics and Chemistry of Minerals, 2010)

The armadillo repeat domain of Apc suppresses intestinal tumorigenesis - Richard C. Crist; Jacquelyn J. Roth; Amy A. Baran; Benjamin J. McEntee; Linda D. Siracusa; Arthur M. Buchberg (Mammalian Genome, 2010)

The roles of social domains, behavioral risk, health care resources, and chlamydia in spatial clusters of US cervical cancer mortality: not all the clusters are the same - Ping Du; Allison Lemkin; Brenda Kluhsman; Jin Chen; Robert E. Roth; Alan MacEachren; Craig Meyers; John J. Zurlo; Eugene J. Lengerich (Cancer Causes & Control, 2010)

A simulation of food‐web interactions leading to rainbow smelt Osmerus mordax dominance in Sparkling Lake, Wisconsin - B. M. Roth; T. R. Hrabik; C. T. Solomon; N. Mercado‐Silva; J. F. Kitchell (Journal of Fish Biology, 2010)
A process‐based simulation model was used to examine the nature and intensity of food‐web interactions that allow Osmerus mordax to dominate invaded lakes. The model simulates food‐web interactions among linked populations of O. mordax , Coregonus artedi and Sander vitreus . Simulations indicated that O. mordax dominate where: (1) adult O. mordax prey on young‐of‐the‐year (YOY) C. artedi , (2) YOY O. mordax negatively affect YOY S. vitreus through competition and (3) adult S. vitreus experience moderate fishing mortality. Osmerus mordax dominated simulations across a broad range of variable values that regulated competition and predation, and displayed threshold responses to increasing angler harvest. Consequently, angler harvest should be carefully managed in lakes susceptible to O. mordax invasions because the alternative could lead to fishery collapse.

N-glycan moieties of the crustacean egg yolk protein and their glycosylation sites - Ziv Roth; Shmuel Parnes; Simy Wiel; Amir Sagi; Nili Zmora; J. Sook Chung; Isam Khalaila (Glycoconjugate Journal, 2010)

RNase 1 genes from the family Sciuridae define a novel rodent ribonuclease cluster - Steven J. Siegel; Caroline M. Percopo; Kimberly D. Dyer; Wei Zhao; V. Louise Roth; John M. Mercer; Helene F. Rosenberg (Mammalian Genome, 2009)

Detection of Peripheral Nerve and Skeletal Muscle Action Currents Using Magnetic Resonance Imaging - Ranjith S. Wijesinghe; Bradley J. Roth (Annals of Biomedical Engineering, 2009)

Ultrasonically-induced Lorentz force tomography - Bradley J. Roth; Kevin Schalte (Medical & Biological Engineering & Computing, 2009)

The potential induced in anisotropic tissue by the ultrasonically-induced Lorentz force - Nancy Tseng; Bradley J. Roth (Medical & Biological Engineering & Computing, 2008)

Mercury and Organic Carbon Dynamics During Runoff Episodes from a Northeastern USA Watershed - P. F. Schuster; J. B. Shanley; M. Marvin-Dipasquale; M. M. Reddy; G. R. Aiken; D. A. Roth; H. E. Taylor; D. P. Krabbenhoft; J. F. DeWild (Water, Air, & Soil Pollution, 2007)

Recent progress in histochemistry - Christian Zuber; Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2007)

Quantifying the effects of voluntary contraction and inter-stimulus interval on the human soleus H-reflex - Richard B. Stein; Kristen L. Estabrooks; Steven McGie; Michael J. Roth; Kelvin E. Jones (Experimental Brain Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Preserved dynamic cerebral autoregulation in the middle cerebral artery among persons with migraine - M. Reinhard; E. Wehrle-Wieland; M. Roth; W. D. Niesen; J. Timmer; C. Weiller; A. Hetzel (Experimental Brain Research, 2007)

Microglial Activation is Required for Aβ Clearance After Intracranial Injection of Lipopolysaccharide in APP Transgenic Mice - Donna L. Herber; Mary Mercer; Lisa M. Roth; Keisha Symmonds; Jessica Maloney; Nedda Wilson; Melissa J. Freeman; Dave Morgan; Marcia N. Gordon (Journal of Neuroimmune Pharmacology, 2007)

The histochemistry and cell biology vade mecum: a review of 2005–2006 - Douglas J. Taatjes; Christian Zuber; Jürgen Roth (Histochemistry and Cell Biology, 2006)

WAY-100635 is a potent dopamine D4 receptor agonist - Benjamin R. Chemel; Bryan L. Roth; Blaine Armbruster; Val J. Watts; David E. Nichols (Psychopharmacology, 2006)

Dose-dependent retrograde facilitation of verbal memory in healthy elderly after acute oral lorazepam administration - Nunzio Pomara; Thomas M. Facelle; Amy E. Roth; Lisa M. Willoughby; David J. Greenblatt; John J. Sidtis (Psychopharmacology, 2006)

Seasonal cycle in vitamin A1/A2-based visual pigment composition during the life history of coho salmon (Oncorhynchus kisutch) - S. E. Temple; E. M. Plate; S. Ramsden; T. J. Haimberger; W.-M. Roth; C. W. Hawryshyn (Journal of Comparative Physiology A, 2006)

Recent progress in histochemistry and cell biology: the state of the art 2005 - Douglas J. Taatjes; Jürgen Roth (Histochemistry and Cell Biology, 2005)

X-ray powder diffraction and 57Fe – Mössbauer spectroscopy of synthetic trioctahedral micas K[Me3] $\langle$ TSi3 $\rangle$ O10(OH)2, Me = Ni2+, Mg2+, Co2+, Fe2+; T = Al3+, Fe3+ - G. J. Redhammer; G. Amthauer; W. Lottermoser; M. Bernroider; G. Tippelt; G. Roth (Mineralogy and Petrology, 2005)

BUBBLE – an Urban Boundary Layer Meteorology Project - M. W. Rotach; R. Vogt; C. Bernhofer; E. Batchvarova; A. Christen; A. Clappier; B. Feddersen; S.-E. Gryning; G. Martucci; H. Mayer; V. Mitev; T. R. Oke; et al. (Theoretical and Applied Climatology, 2005)

The highly efficacious actions of N-desmethylclozapine at muscarinic receptors are unique and not a common property of either typical or atypical antipsychotic drugs: is M1 agonism a pre-requisite for mimicking clozapine?s actions? - Marilyn A. Davies; Beth Ann Compton-Toth; Sandra J. Hufeisen; Herbert Y. Meltzer; Bryan L. Roth (Psychopharmacology, 2005)

CHARACTERISTICS OF A HUMAN PROSTATE STROMAL CELL LINE RELATED TO ITS USE IN A STROMAL–EPITHELIAL COCULTURE MODEL FOR THE STUDY OF CANCER CHEMOPREVENTION - LENA DIAW; MARK ROTH; DEBRA A. SCHWINN; MARY E. d'ALELIO; LISA J. GREEN; JOSEPH A. TANGREA (In Vitro Cellular & Developmental Biology - Animal, 2005)

Polymorphic variation of CYP1A1 is associated with the risk of gastric cardia cancer: a prospective case?cohort study of cytochrome P-450 1A1 and GST enzymes - Mark J. Roth; Christian C. Abnet; Laura Lee Johnson; Steven D. Mark; Zhi Wei Dong; Philip R. Taylor; Sanford M. Dawsey; You-Lin Qiao (Cancer Causes & Control, 2004)

Conversion of single-layered Scots pine monocultures into close-to-nature mixed hardwood forests: effects on parasitoid wasps as pest antagonists - Alexander Jkel; Mechthild Roth (European Journal of Forest Research, 2004)

A note to our authors - Jrgen Roth; Detlev Drenckhahn (Histochemistry and Cell Biology, 2004)

Cardiac Optical Mapping Under a Translucent Stimulation Electrode - Joy Liau; John Dumas; Deborah Janks; Bradley J. Roth; Stephen B. Knisley (Annals of Biomedical Engineering, 2004)

Examination of Physical and Regulatory Variables Leading to Small Dam Removal in Wisconsin - Cailin H. Orr; Brian M. Roth; Kenneth J. Forshay; James D. Gonzales; Michael M. Papenfus; Rebecca D.G. Wassell (Environmental Management, 2004)

Ultrastructural analysis of transitional endoplasmic reticulum and pre-Golgi intermediates: a highway for cars and trucks - Jing-Yu Fan; Jrgen Roth; Christian Zuber (Histochemistry and Cell Biology, 2003)

Spatiotemporal expression patterns of sialoglycoconjugates during nephron morphogenesis and their regional and cell type-specific distribution in adult rat kidney - Christian Zuber; Harry C. Winter; Irwin J. Goldstein; Jrgen Roth; James C. Paulson; Valeriu Toma (Histochemistry and Cell Biology, 2003)

Using Environmental Stressor Information to Predict the Ecological Status of Maryland Non-tidal Streams as Measured by Biological Indicators - J. H. Vølstad; N. E. Roth; G. Mercurio; M. T. Southerland; D. E. Strebel (Environmental Monitoring and Assessment, 2003)

Magneto-encephalogram artifacts caused by electro-encephalogram electrodes - R. Murdick; B. J. Roth (Medical & Biological Engineering & Computing, 2003)

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)

Limnological effects of anthropogenic desiccation of a large, saline lake, Walker Lake, Nevada - Marc W. Beutel; Alex J. Horne; James C. Roth; Nicola J. Barratt (Hydrobiologia, 2001)

How Epicardial Electrodes Influence the Transmembrane Potential During a Strong Shock - Salil G. Patel; Bradley J. Roth (Annals of Biomedical Engineering, 2001)

Histochemistry and Cell Biology announces: All Color Pages Free of Charge - J. Roth; D. Drenckhahn (Histochemistry and Cell Biology, 2001)

plastids undifferentiated, a nuclear mutation that disrupts plastid differentiation in Zea mays L. - Ronelle Roth; Ruairidh J. Sawers; Helen L. Munn; Jane A. Langdale (Planta, 2001)

Application of a lectin from the mushroom Polysporus squamosus for the histochemical detection of the NeuAcα2,6Galβ1,4Glc/GlcNAc sequence of N-linked oligosaccharides: a comparison with the Sambucus nigra lectin - Valeriu Toma; Christian Zuber; Harry C. Winter; Irwin J. Goldstein; Jürgen Roth (Histochemistry and Cell Biology, 2001)

The crystal and magnetic structure of Li-aegirine LiFe 3+ Si 2 O 6 : a temperature-dependent study - G. J. Redhammer; G. Roth; W. Paulus; G. André; W. Lottermoser; G. Amthauer; W. Treutmann; B. Koppelhuber-Bitschnau (Physics and Chemistry of Minerals, 2001)

Distribution of Inorganic Mercury in Sacramento River Water and Suspended Colloidal Sediment Material - D. A. Roth, H. E. Taylor, J. Domagalsk (Archives of Environmental Contamination and Toxicology, 2001)

Structure and Mössbauer spectroscopy of barbosalite Fe 2+ Fe 3+ 2 (PO 4 ) 2 (OH) 2 between 80 K and 300 K - G. J. Redhammer; G. Tippelt; G. Roth; W. Lottermoser; G. Amthauer (Physics and Chemistry of Minerals, 2000)

Comparison of either norepinephrine-uptake inhibitors or phentermine combined with serotonergic agents on food intake in rats - N. E. Rowland; M. Marshall; J. D. Roth (Psychopharmacology, 2000)

Expression of oligo/polyα2,8-linked deaminoneuraminic acid and megalin during kidney development and maturation: mutually exclusive distribution with polyα2,8-linked N -acetylneuraminic acid of N-CAM - Martin Ziak; J. Roth (Histochemistry and Cell Biology, 1999)

Mechanism for polarisation of cardiac tissue at a sealed boundary - B. J. Roth (Medical & Biological Engineering & Computing, 1999)

Dopamine D 4 receptor antagonist reversal of subchronic phencyclidine-induced object retrieval/detour deficits in monkeys - J. D. Jentsch; Jane R. Taylor; D. Eugene Redmond Jr; John D. Elsworth; Kenneth D. Youngren; Robert H. Roth (Psychopharmacology, 1999)

Dependence of cardiac strength-interval curves on pacing rate - J. A. Bennett; B. J. Roth (Medical & Biological Engineering & Computing, 1999)

Two-dimensional gel analysis of apoptosis-specific p53 isoforms induced by 2-methoxyestradiol in human lung cancer cells - T. Mukhopadhyay; J. A. Roth; S. A. Acosta; S. A. Maxwell (Apoptosis, 1998)

Improved mRNA in situ hybridization on formaldehyde-fixed and paraffin-embedded tissue using signal amplification with different haptenized tyramides - E. J. M. Speel; Parvin Saremaslani; Jürgen Roth; Anton H. N. Hopman; Paul Komminoth (Histochemistry and Cell Biology, 1998)

Unconventional antigen retrieval for carbohydrate and protein antigens - Bruno Guhl; Martin Ziak; J. Roth (Histochemistry and Cell Biology, 1998)

Modeling of Spreading Cortical Depression Using a Realistic Head Model - Ranjith S. Wijesinghe; Bradley J. Roth; Norman Tepley (Brain Topography, 1998)

Prefrontal cortical involvement in phencyclidine-induced activation of the mesolimbic dopamine system: behavioral and neurochemical evidence - J. David Jentsch; A. Tran; Jane R. Taylor; Robert H. Roth (Psychopharmacology, 1998)

Colonoscope flexural rigidity measurement - J. A. Wehrmeyer; J. A. Barthel; J. P. Roth; T. Saifuddin (Medical & Biological Engineering & Computing, 1998)

Tubules of the trans Golgi apparatus visualized by immunoelectron microscopy - J. Roth; Douglas J. Taatjes (Histochemistry and Cell Biology, 1998)

Maryland Biological Stream Survey: Development of a Fish Index of Biotic Integrity - N. Roth; M. Southerland; J. Chaillou; R. Klauda; P. Kazyak; S. Stranko; S. Weisberg; L. Hall; R. Morgan II (Environmental Monitoring and Assessment, 1998)

Maryland Biological Stream Survey: A State Agency Program to Assess the Impact of Anthropogenic Stresses on Stream Habitat Quality and Biota - R. Klauda; P. Kazyak; S. Stranko; M. Southerland; N. Roth; J. Chaillou (Environmental Monitoring and Assessment, 1998)

The Effects of Acid Precipitation and Ozone on the Ectomycorrhizae of Red Spruce Saplings - Diana R. Roth; Timothy J. Fahey (Water, Air, & Soil Pollution, 1998)

TRP64ARG β3-adrenergic receptor and obesity in Mexican Americans - K. Silver; Braxton D. Mitchell; Jeremy Walston; J. D. Sorkin; Michael P. Stern; Jesse Roth; A. R. Shuldiner (Human Genetics, 1997)

Fever and production of cytokines in response to repeated injections of muramyl dipeptide in guinea-pigs - Joachim Roth; Stephen J. Hopkins; Margaret E. Hoadley; Anke Tripp; Tunai Aslan; Birgit Störr; Giamal N. Luheshi; E. Zeisberger (Pflügers Archiv - European Journal of Physiology, 1997)

Trisomy associated with loss of maturation capacity in a long-term embryogenic culture of Abies alba - R. Roth; I. Ebert; J. Schmidt (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Effect of a perfusing bath on the rate of rise of an action potential propagating through a slab of cardiac tissue - Bradley J. Roth (Annals of Biomedical Engineering, 1996)

Magnetic stimulation of axons in a nerve bundle: Effects of current redistribution in the bundle - Srikantan S. Nagarajan; Dominique M. Durand; Brandley J. Roth; Ranjith S. Wijesinghe (Annals of Biomedical Engineering, 1995)

A theoretical comparison of electric and magnetic stimulation of the brain - J. M. Saypol; B. J. Roth; L. G. Cohen; M. Hallett (Annals of Biomedical Engineering, 1992)

A comparison of two boundary conditions used with the bidomain model of cardiac tissue - Bradley J. Roth (Annals of Biomedical Engineering, 1991)

A theoretical comparison of electric and magnetic stimulation of the brain - Joshua M. Saypol; Bradley J. Roth; Leonardo G. Cohen; Mark Hallett (Annals of Biomedical Engineering, 1991)

The electrical potential produced by a strand of cardiac muscle: A bidomain analysis - Bradley J. Roth (Annals of Biomedical Engineering, 1988)

Longitudinal resistance in srands of cardiac muscle - Bradley J. Roth (Annals of Biomedical Engineering, 1988)

Carbon dioxide exchange across the walls of arterioles: Implication for the location of the medullary chemoreceptors - J. Milton Adams; Christine Banka; Walter E. Wojcicki; Allan C. Roth (Annals of Biomedical Engineering, 1988)

A comparison of two models for calculating the electrical potential in skeletal muscle - Bradley J. Roth; Frans L. H. Gielen (Annals of Biomedical Engineering, 1987)

Percutaneous implant devices - Vert Mooney; S. Andrew Schwartz; Andrew M. Roth; Michael J. Gorniowsky (Annals of Biomedical Engineering, 1977)

Timing applications for control of potato aphids on Long Island - W. A. Rawlins; R. W. Roth; J. E. Dewey (American Journal of Potato Research, 1943)